2010
DOI: 10.1073/pnas.0914030107
|View full text |Cite
|
Sign up to set email alerts
|

Micron-scale holes terminate the phage infection cycle

Abstract: Holins are small phage-encoded proteins that accumulate harmlessly in the cytoplasmic membrane during the infection cycle until suddenly, at an allele-specific time, triggering to form lethal lesions, or "holes." In the phages λ and T4, the holes have been shown to be large enough to allow release of prefolded active endolysin from the cytoplasm, which results in destruction of the cell wall, followed by lysis within seconds. Here, the holes caused by S105, the λ-holin, have been captured in vivo by cryo-EM. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
85
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 42 publications
8
85
1
Order By: Relevance
“…3 Briefly, the host RY16504 carrying the plasmid p0 was induced for 60 min with 1 mM IPTG at A550 ¼ 0.4 and 5 lL of culture was immediately applied to holey carbon films (C-Flat, Protochips). Grids were plunge frozen in liquid ethane using an FEI Vitrobot.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…3 Briefly, the host RY16504 carrying the plasmid p0 was induced for 60 min with 1 mM IPTG at A550 ¼ 0.4 and 5 lL of culture was immediately applied to holey carbon films (C-Flat, Protochips). Grids were plunge frozen in liquid ethane using an FEI Vitrobot.…”
Section: Electron Microscopymentioning
confidence: 99%
“…2 First, after accumulating harmlessly in the IM throughout late gene expression, the holin S105, encoded by S, suddenly forms extremely large, irregular holes. 3 Besides terminating macromolecular synthesis and virion assembly, this event allows the lambda endolysin R, a soluble cytoplasmic transglycosylase, to escape to the periplasm, thus allowing the second step, degradation of the PG, to occur. The destruction of the PG is followed by the third step, which requires the products of the last two genes, Rz and Rz1.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent cryo-electron microscopy and tomography studies revealed that the lesions caused by holin S105 of phage l could be visualized as interruptions in the bilayer spanning very large areas of the cytoplasmic membrane, averaging >350 nm in diameter (Dewey et al 2010). Assuming these lesions correspond to the holes, this latter observation fully accounted for the ability of holins to allow the rapid, nonspecific escape of proteins not only of endolysins, of which the l R endolysin, a soluble, 15-kDa monomeric protein is typical, but also of much larger proteins, including the ;500-kDa R-LacZ chimeras (Dewey et al 2010). However, the lesions that are formed by the Bax proteins in the bacterial cytoplasmic membrane do not appear to be of the near micron-scale holes like those formed by the S105 holin, since they could not be observed using cryo-electron microscopy at a 50-nm resolution (data not shown).…”
Section: Active Bax and Bak As Functional Holins Mechanistically Linmentioning
confidence: 99%
“…This event, called triggering, occurs at an allele-specific time. The lesions formed by canonical holins are very large, with diameters of micrometer-scale, allowing the escape of prefolded phage endolysins from the cytoplasm (2,3). However, another important class of holins, the pinholins, form holes too small for the passage of protein.…”
mentioning
confidence: 99%